Regional specialization and labor mobility: An empirical analysis of German microdata for 2000-2010 - Alexander Cordes (Expertenkommission Forschung und Innovation (EFI), 2015)
Spatial patterns of industrial strengths are of increasing interest since the rise of "smart specialization" strategies requires the identification of promising technologies and industries which might emanate from existing structures. The attraction of skilled labor is supposed to play an important role in this process: first, in order to strengthen the innovation potential at the interface between existing and pro-spective industries, and second, as a quantitative contribution to industrial employment growth. Against this background, this study analyses regional specialization and employment growth in German regions and provides evidence for the employees' origin. The approach is based on micro data of firms and employees for the period from 2000 to 2010. Firm level data is used to calculate specialization measures for 96 planning regions and 35 industries. Two indices are constructed for three major sectors in order to illustrate the spatial pattern. These broader sectors are non-knowledge intensive manufacturing (nkim), knowledge intensive manufacturing (kim), and knowledge intensive services (kis). Mappings of indices and employment shares of single industries provide detailed evidence on major and minor locations in Germany.
Keywords: 330